Advancing endometrial cancer treatment: exploring immunotherapy and tyrosine kinase inhibitors through clinical cases - Vanda Salutari (Drugs in Context)
Endometrial cancer (EC) is the most common gynaecological malignancy in developed countries, with advanced- stage disease posing significant therapeutic challenges. Standard treatments, including surgery, radiotherapy and chemotherapy, have limited efficacy in recurrent or metastatic cases, necessitating novel therapeutic approaches. Recent molecular classifications of EC have identified subtypes with distinct prognostic and therapeutic implications, particularly those with high immunogenicity. Immunotherapy, specifically immune-checkpoint inhibitors targeting PD-1/ PD-L1, has transformed EC treatment. The combination of pembrolizumab, an anti-PD-1 monoclonal antibody, and lenvatinib, a tyrosine kinase inhibitor (TKI), has demonstrated superior efficacy over chemotherapy in the pivotal KEYNOTE-775 trial, significantly improving progression-free and overall survival in advanced EC. Additionally, dostarlimab has shown promise as a monotherapy for mismatch repair-deficient EC, expanding treatment options. This special series in Drugs in Context explores these advancements through clinical case studies, highlighting real-world applications of immunotherapy and TKIs. Cases illustrate treatment responses, challenges in managing toxicities and the evolving role of molecular profiling in personalizing therapy. As research progresses, integrating immunotherapy and TKIs into routine practice is expected to improve outcomes for patients with advanced EC, offering new hope in a previously limited therapeutic landscape.